Pemanfaatan Minyak Jelantah Dalam Pembuatan Lilin Aromaterapi Sebagai Salah Satu Ide Usaha di Desa Tanah Seribu Binjai - Irda Auliya Hadi Lubis; Nurul Choriah Tumanggor; Nur Elisah Nasution; Khairunnisa Tanjung; Tanti Jumaisyaroh Siregar; Ella Andhany (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Used cooking oil is used oil that can be obtained from household activities. Utilizing used cooking oil as a basic ingredient for making aromatherapy candles which can be used as a business opportunity. Scented candles are candles that contain aromatic ingredients that can be used for refreshing, relaxing and treating headaches. This research uses a demonstration method delivered with practice on how to make aromatherapy in the form of candles. The aim of this training activity is so that people can practice it independently and can open up business opportunities that have large sales value. This activity was carried out in Tanah Seribu Village, South Binjai District, Binjai City, North Sumatra, on Sunday 20 August 2023 offline. A total of ±15 people, the participants were women from Tanah Seribu Village, Binjai. This community service is carried out as a form of student concern for the community and adds to student experiences that are not available on campus